Sosialisasi Pengalokasian Dana Tepat Guna Dan Sasaran Dalam Kehidupan Ummat Di SMA Tri Dharma Palembang - Meriyati Meriyati; Amir Salim (AKM, 2020)
The second bank activity after collecting funds from the wider community in the form of deposits, savings and time deposits is to channel these funds back to the people who need them. The activity of channeling funds is also known as fund allocation. The allocation of funds can be realized in the form of loans or better known as loans to conventional banks and financing to sharia-based banks. Both types of distribution of funds have advantages and disadvantages of each. Giving credit or financing can be said to be economic stability because with the credit given will increase the amount of goods needed by the community. Then credit can also help in exporting domestic goods abroad so as to increase the country's foreign exchange. To increase the excitement of trying, for the recipient of the credit will certainly be able to increase the excitement of doing business, especially for the customer who is mediocre capital. To increase income distribution. The more credit / financing distributed, the better, especially in terms of increasing income. However, these two types of products both credit and financing will be the best solution for the Ummah if the allocation of these funds is used appropriately and with the right target.